The Effect of Watching Television On The Behavioral development of 4th graders at SDN 3 Gesik - Yunita Rizqianthi; nala nandana undiana (Universitas Pendidikan Indonesia, 2021)
Indonesia has been able to make advanced technologies, one of which is television. The impressions on television have been able to attract the audience’s interest, and make him addicted to watching the existing programs. Especially for the children at SDN 3 GESIK who are inseparable from their activities. In this study, researchers used a Cultivation Theory approach using quantitative research methods. The cultivation approach was used to see the effect of watching televisiom on the behavioral development of 4th graders at SDN 3 GESIK. The data used in this study is the result oh the distribution of the google form created by the researcher which was distributed by the parents of the 4th graders at SDN 3 GESIK. The result of the data indicate that there is a negative and positive influence of watching television on the behavioral development of at 4th graders at SDB 3 GESIK